2013
DOI: 10.1016/s0254-6272(13)60122-3
|View full text |Cite
|
Sign up to set email alerts
|

Image formation of brain function in patients suffering from knee osteoarthritis treated with moxibustion

Abstract: The influence of moxibustion on obvious changes in brain regions basically conforms to the way that pain and warmth is transmitted in the body, and the activation of sensitive systems in the body may be objective evidence of channel transmission. The regulation of brain function by moxibustion is not in a single brain region but rather in a network of many brain regions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 1 publication
1
13
0
Order By: Relevance
“…ONFH may lead to intractable pain and the functional disability of the hip joint. Chronic pain and gait abnormality could influence the spatial patterns of intrinsic brain activity (Xie et al, 2013 ; Chen et al, 2015 ; Flodin et al, 2016 ; Ryan et al, 2018 ; Schrepf et al, 2018 ). Our study investigated the ONFH-related changes in the intrinsic or spontaneous brain activity by measuring the ALFF values of resting-state fMRI signals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ONFH may lead to intractable pain and the functional disability of the hip joint. Chronic pain and gait abnormality could influence the spatial patterns of intrinsic brain activity (Xie et al, 2013 ; Chen et al, 2015 ; Flodin et al, 2016 ; Ryan et al, 2018 ; Schrepf et al, 2018 ). Our study investigated the ONFH-related changes in the intrinsic or spontaneous brain activity by measuring the ALFF values of resting-state fMRI signals.…”
Section: Discussionmentioning
confidence: 99%
“…A study based on the moxibustion treatment of knee osteoarthritis demonstrated increased fractional amplitude of low-frequency fluctuation (fALFF) values in the bilateral cerebrum, extra-nucleus, left cerebellum, and white matter. Simultaneously, the fALFF values of the precentral gyrus (PreCG), frontal lobe, and occipital lobe were found to be decreased (Xie et al, 2013 ). In rheumatoid arthritis patients, Flodin et al ( 2016 ) reported that the supplementary motor areas, midcingulate cortex, and primary sensorimotor cortex exhibited enhanced functional connectivity.…”
Section: Introductionmentioning
confidence: 99%
“…Although the exact biologic mechanisms of ALFF are still unclear, it has been widely used in studies for neuropsychological diseases ( 24 26 ) due to the fact that altered ALFF is directly related to abnormal regional neuronal activity ( 26 , 27 ). Similar algorithms have been applied to detect the influence of moxibustion on functional brain alterations in patients with KOA between pre- and post-treatment ( 28 ). Thus, ALFF is potentially valuable for uncovering the mechanism underlying the changes in brain function in the older patients with KOA before and after TKA.…”
Section: Discussionmentioning
confidence: 99%
“…However, the recipient was able to sense the trans-segmental heat in the distant parts. Xie et al [4] used fMRI to study the responses and found that the brain function regulation of heat-sensitization responses did not coordinate through a single brain region but a network composed of multiple brain regions, especially in the prefrontal and island cortices. Liao et al [13] used high-density electroencephalogram (EEG) to test the EEG characteristics of moxibustion-induced heat-sensitization responses.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous studies, most reactions to heat-sensitization moxibustion, which were described by the participants, were observed directly or collaterally relating with neurological system; noticeably the brain perception was spotted [3]. A study of functional magnetic resonance imaging (fMRI) also showed that heat-sensitization response was manifested in the changes of brain activities in prefrontal cortex [4]. Therefore, we hypothesize that neurological system is involved in moxibustion-induced heat-sensitization responses.…”
Section: Introductionmentioning
confidence: 99%